Evaluation of obesity-oriented nutrition and lifestyle education tool kit for elementary school children in Lebanon - Maatouk, Kholoud Ahmad (Beirut American University of Beirut - Faculty of Agricultural and Food Sciences - Department of Nutrition and Food Science., 2008)
Childhood obesity is an increasing worldwide epidemic. It has been demonstrated that the best way to target childhood obesity is through prevention with the bes t place being schools. In Lebanon, no school-based interventions have been repor ted in literature. A pretest post-test one group evaluation design was conducted to determine the e ffect of an eight-week culturally appropriate nutritional educational program on nutritional knowledge, food choice selection, sedentary activity and physical a ctivity, as well as anthropometric measurements. One school was randomly selected from each of the three sectors: private, free p rivate and public schools. Grades 3, 4 and 5 were targeted, including 160 partic ipants. Anthropometrics measurements (BMI and waist circumference), and SPAN and knowledge questionnaires were used to assess the studied variables at baseline, immediately (Phase I), two weeks (Phase II) and six months (Phase III) after in tervention. Comparative analyses were done to test the change in studied variabl es across time between 1) genders and 2) among school types. Compared to baseline, at Phase I significant improvement was observed in: knowle dge scores (overall), sedentary activity scores (overall), physical activity sco re (type of school) and meat consumption scores (overall, private schools and fe males). At Phase III, retention of improvement in knowledge score (overall) was observed. The intervention had no effect on the prevalence of obesity. This study was able to demonstrate the effect of nutritional educational program on improving nutritional knowledge, enhancing meat consumption and decreasing s edentary activity for the overall sample. The increase in overall knowledge was retained six month post intervention.
: Mémoire
Keywords: Children; Cycle primaire; Education Sanitaire; Elementary Education; Enfants; Evaluation Scolaire; Health education Overweight; School Evaluation; Surpoids